Exploring Students’ Perception on The Implementation of a Web-Based Materials in Intensive Reading Class - Malasari, Susanti; Fortinasari, Paulina Besty (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2025)
Intensive Reading is one of reading subjects learned by English Department students. This course is a reading activity to find information and understand the contents of various reading texts. Good reading skills will enable students find and understand information from various texts proficiently. Besides knowing and applying reading strategies, students can improve their reading skills by doing reading practice continuously. Therefore, students need to have an easy access of various texts that are used as intensive reading materials. Website is one of the media that can be used to provide intensive reading materials. This is a descriptive qualitative research that is aimed to explore students’ perception on the implementation of a web-based materials in intensive reading class. The participants were the second semester of English Department students learned intensive reading. The data were obtained from observation, interview, and documentation. The findings showed that students have positive perception on the implementation of a web-based materials in intensive reading class. It was found that the implementation of websites can motivate students in learning to read, help students improve their reading comprehension, and form students’ reading habits.